Spatial, seasonal and interannual variability of supraglacial ponds in the Langtang Valley of Nepal, 1999–2013 - Miles, Evan; Willis, Ian; Arnold, Neil; Steiner, Jakob; Pellicciotti, Francesca (Journal of Glaciology, 2017)
Supraglacial ponds play a key role in absorbing atmospheric energy and directing it to the ice of debris-covered glaciers, but the spatial and temporal distribution of these features is not well documented. We analyse 172 Landsat TM/ETM+ scenes for the period 1999–2013 to identify thawed supraglacial ponds for the debris-covered tongues of five glaciers in the Langtang Valley of Nepal. We apply an advanced atmospheric correction routine (Landcor/6S) and use band ratio and image morphological techniques to identify ponds and validate our results with 2.5 m Cartosat-1 observations. We then characterize the spatial, seasonal and interannual patterns of ponds. We find high variability in pond incidence between glaciers (May–October means of 0.08–1.69% of debris area), with ponds most frequent in zones of low surface gradient and velocity. The ponds show pronounced seasonality, appearing in the pre-monsoon as snow melts, peaking at the monsoon onset at 2% of debris-covered area, then declining in the post-monsoon as ponds drain or freeze. Ponds are highly recurrent and persistent, with 40.5% of pond locations occurring for multiple years. Rather than a trend in pond cover over the study period, we find high interannual variability for each glacier after controlling for seasonality.